A Conceptual Analysis of Labels Referring to Brand Co-Creation - Tähtinen Jaana; Suomi Kati (Edward Elgar Publishing, 2022)
As research on brand co-creation is rapidly increasing, it is time to take a look at its theoretical grounding; the current conceptual language. This chapter examines the conceptual state of brand co-creation research by focusing on i) the definitions of the concepts and ii) the descriptions of the terms used to refer to brand co-creation. The aim is to reveal and clarify any conceptual confusions and to disentangle the concept combinations used. We apply Conceptual Analysis Method, which is also further developed in the process. As an outcome, the chapter offers conceptual maps of the five most used concepts. The maps illuminate the complexity of the phenomenon and aid future research to bolster multi-vocal theory development.
Research handbook on brand co-creation: Theory, practice, and ethical implications